The Anatomy of the World - Germek, Magdalena (Filozofski vestnik, 2022)
In this article, we discuss Badiou’s concept of the world through the somewhat unusual metaphor of “the anatomy of the world”. The anatomy of the world allows us to approach the concept of the world through the idea of ​​its constitution, architecture, structure – its anatomy. But as we show in the first part of the text, in order to derive the anatomy of the world, we need a corpse of the world – the world must die. Following the philosophy of Alain Badiou, we demonstrate that the world in its objective existence is indifferent to the question of life and death. Whether the world lives or dies depends only on the realisation of the truth procedures in the world on the basis of which the world is subjectivised. The world suffers from mortifying impulses, as the reactive and obscure forms of subjectivity actively work against the realisation of truths in the world. Through the artistic presentations of anatomy by Rembrandt van Rijn and John Donne, we also elaborate the tense relationship between the corpse of the world (from the perspective of the scientific procedure of truth) and the life of the world (from the perspective of the artistic procedure of truth). Although art often sees science as something that kills the world, our final point is that the world can also come to life through science.